Pengaruh Reward dan Insentif terhadap Kepuasan Kerja Agen Platinum PT X Jakarta - Suriandhi, Denny (Journal of Economics & Business UBS, 2020)
The purpose of this study is to analyze the influence of rewards and incentives on the satisfaction of platinum agent PT X DKI Jakarta area. This study was included in the category of quantitative descriptive research. This study uses individuals for their unit of analysis, answer questions based on responses from individuals which belong to the category of platinum agents in the area of DKI Jakarta. The type of data used was the primary data. The population in this study were all of platinum agents in DKI Jakarta area which number as many as 20 people, which will be also used as sample by Purposive Sampling technique. The research instrument used questionnaire with Likert scale. Data analysis includes validation and reliability test. Statistical analysis using multiple linear regression test, coefficient of determination test, partial test (t test), and simultaneous test (F test). The result of the research shows that reward influence partially to the satisfaction of platinum agents PT X in DKI Jakarta area, incentive partially influence to satisfaction of platinum agents PT X in DKI Jakarta area, and reward and incentive affect simultaneously to the satisfaction of platinum agents PT X in DKI Jakarta area.